(untitled) (Jurnal Kemanusiaan, 2017)
ABSTRACT The development of multimedia technology in Malaysia has improved significantly the government administration system. The Malaysian government is also providing encouragement towards this development by establishing Multimedia Super Corridor (MSC). However, what is the preparation of the Muslim community in Malaysia to embrace the new development in multimedia technology? To what extent Muslims are ready to face the challenges in the wake of rapid development of technology? This article attempts to discuss the implications of multimedia technology in Malaysia over the identity of the Muslim community. The development of multimedia technology in Malaysia and the views of some experts discussed critically in order to assess the implications of this multimedia technology. ABSTRAK Perkembangan teknologi multimedia di Malaysia sangat memberangsangkan dalam meningkatkan sistem pentabiran kerajaan. Kerajaan Malaysia turut memberikan galakan positif ke arah perkembangan ini dengan menubuhkan pusat Multimedia Super Corridor (MSC). Namun, apakah persiapan masyarakat islam di Malaysia terhadap perkembangan teknologi multimedia ini? Sejauh manakah umat islam bersedia menghadapi cabaran-cabaran moden dalam ledakan teknologi terkini dalam kehidupan mereka? Artikel ini cuba untuk membincangkan implikasi teknologi multimedia di Malaysia ke atas identiti masyarakat islam. Analisis pembangunan teknologi multimedia di Malaysia dan pandangan-pandangan dari beberapa pakar cuba dibincangkan secara kritis untuk memberi penilaian terhadap implikasi teknologi multimedia ini.